How watch the dogs? Assessing the portuguese credit co-operative system governance - Cabo, Paula (2014)
In recent years the importance of corporate governance has rising new attention as the 2008 financial crisis illustrates. As other enterprises, cooperatives are subject to pressure for greater efficiency and change in corporate governance. “It is important for cooperatives to consider corporate governance within the framework of their cooperative origins … building up an effective system of internal control” (Pallervo, 2000:3). The agricultural credit cooperative system in Portugal is made up of an integrated system (SICAM) of two types of cooperatives: the central and the singles (associated). The singles are autonomous local banks, called Caixas de Crédito Agrícola Mútuo (CCAM) with their own capital, general assembly and supervision and administration bodies. The SICAM governance integrates a two-tier system control mechanisms: the singles and the SICAM control mechanisms. The singles use a model in which there is both a supervisory board and a board of directors formed by the member-owners. They represent the general assembly interests monitoring CCAM management. An efficient control dictates that CCAM performance and the turnover of the supervisory board and board of directors’ members should be negatively related. However, several factors, as the increasing complexity of banking activity and the decline in member participation in general assembly [as illustrated by Spear (2004) user based co-operatives frequently have a very low level of member participation at general assembly] affects it’s efficacy. SICAM mechanisms lay on Central CCAM supervision role and on cooperative merger activity. Although Bank of Portugal are the responsible for the banking sector supervision, regarding SICAM associates the law delegates great part of these functions in the Central CCAM. Central CCAM is empowered to intervene in the associates, by the assignment of a representative to track CCAM management or the nomination of provisory directors. When it verifies a disequilibrium situation that can jeopardize the CCAM daily running, the solvency is at risk or serious irregularities occur. Plus, when the associated is in (risk of) financial disequilibrium and unfollow Central CCAM guidelines, Central CCAM can dismiss total or part of the associated management and supervision boards and assign provisory directors to them (Cabo and Rebelo, 2010). Long term inefficiencies are often solved by the CCAM incorporation (or merger with) a more efficient CCAM. This paper intends to illustrate how SICAM internal control is organized and assess its efficacy. Using data from 1995-2009 period, and multinomial logit model the paper analyse the relation between CCAM performance and the various control mechanisms operating in SICAM. The results show up the importance of the Central CCAM supervision task in the monitoring their associates and it effect over SICAM overall performance.